Understanding the Person through Narrative - Joanne M. Hall; Jill Powell (Nursing Research and Practice)
Mental health nurses need to know their clients at depth, and to comprehend their social contexts in order to provide holistic care. Knowing persons through their stories, narratives they tell, provides contextual detail and person-revealing characteristics that make them individuals. Narratives are an everyday means of communicating experience, and there is a place for storytelling in nearly all cultures. Thus narrative is a culturally congruent way to ascertain and understand experiences. This means the nurse should ask questions such as “How did that come about?” versus why questions. A narrative approach stands in contrast to a yes/no algorithmic process in conversing with clients. Eliciting stories illustrates the social context of events, and implicitly provides answers to questions of feeling and meaning. Here we include background on narrative, insights from narrative research, and clinical wisdom in explaining how narratively understanding the person can improve mental health nursing services. Implications for theory, practice, and research are discussed.